Biomineralized PEEK cages containing osteoinductive CaP bioceramics promote spinal fusion in goats - Qiujiang Li; Bowen Hu; Linan Wang; Lei Wang; Cong Feng; Zhuang Zhang; Zhipeng Deng; Yang Xiao; Bo Yuan; Xiangdong Zhu; Xiangfeng Li; Xi Yang; et al. (Bioactive Materials)
Interbody fusion devices are critical in spinal surgery to restore spinal stability, reduce pain and improve function. Polyetheretherketone (PEEK) has become a commonly used alternative material for fusion cages owing to its excellent mechanical properties and biocompatibility, but its biological inertness limits bone regeneration and may lead to poor fusion. In this study, a novel strategy for preparing bioactive biomineralized PEEK cages was developed using a unique combination of osteoinductive CaP bioceramic fillings in the cage window, acid sulfonation and simulated body fluid incubation. In vitro experiments showed that biomineralized PEEK cages and CaP bioceramics regulate immunity and promote angiogenesis and bone integration via activation of hypoxia-inducible factor 1-alpha and cyclic guanosine monophosphate/protein kinase G signaling pathways. In vivo goat spinal fusion experiments demonstrated that PEEK cages filled with CaP bioceramics resulted in good bone growth and spinal fusion. Therefore, the high mechanical strength and good biocompatibility of biomineralized PEEK cages, together with the excellent bioactivity and degradation properties of CaP bioceramics, provide an ideal microenvironment for bone fusion. The development of this composite material not only addresses some of the limitations of existing fusion devices but also will facilitate the development of spinal fusion technology.